Applications of nano-materials in diverse dentistry regimes. Issue 26 (20th April 2020) - Foong, Loke Kok; Foroughi, Mohammad Mehdi; Mirhosseini, Armita Forutan; Safaei, Mohadeseh; Jahani, Shohreh; Mostafavi, Maryam; Ebrahimpoor, Nasser; Sharifi, Maryam; Varma, Rajender S.; Khatami, Mehrdad
Abstract : The present review paper provided an overall overview of various kinds, synthesis techniques, characteristics, features and uses of nanomaterials. Abstract : Research and development in the applied sciences at the atomic or molecular level is the order of the day under the domain of nanotechnology or nano-science with enormous influence on nearly all areas of human health and activities comprising diverse medical fields such as pharmacological studies, clinical diagnoses, and supplementary immune system. The field of nano-dentistry has emerged due to the assorted dental applications of nano-technology. This review provides a brief introduction to the general nanotechnology field and a comprehensive overview of the synthesis features and dental uses of nano-materials including current innovations and future expectations with general comments on the latest advancements in the mechanisms and the most significant toxicological dimensions.